Effect of Fortification of Anchovy Flour on Calcium Content, Orgnoleptic Quality and Shelf Life of Canned Tuna Porridge Products - Tangke, Umar; Talib, Ahmad; Daeng, Ruslan A (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
This research was conducted with the aim of knowing the effect of anchovy meal fortification on organoleptic quality and determining the best product based on a completely randomized design and Bayes method. The results showed that based on the results of the analysis using the Bayes method, canned tuna porridge with 3% anchovy flour fortification (A1 treatment) was the best product with a weight of 4.00 tilapia, followed by treatments A0 and A2 with a weighted value of 3.23 each. and 2.62.